Modulation of Gonadotropin-Releasing Hormone Pulse Generator Sensitivity to Progesterone Inhibition in Hyperandrogenic Adolescent Girls—Implications for Regulation of Pubertal Maturation - Blank, Susan K.; McCartney, Christopher R.; Chhabra, Sandhya; Helm, Kristin D.; Eagleson, Christine A.; Chang, R. Jeffrey; Marshall, John C. (The journal of clinical endocrinology and metabolism, 2009)
Context: Adult women with polycystic ovary syndrome (PCOS) have decreased GnRH pulse generator sensitivity to progesterone (P)-mediated slowing. This defect is androgen mediated because it is reversed with androgen receptor blockade. Adolescent hyperandrogenism often precedes PCOS. Objective: The aim of the study was to evaluate GnRH pulse generator sensitivity to P-mediated slowing in normal and hyperandrogenic girls. Design: We conducted a controlled interventional study. Setting: The study was conducted in a general clinical research center. Participants: A total of 26 normal control (NC) and 26 hyperandrogenic (HA) girls were studied. Intervention: Frequent blood sampling was performed for 11 h to assess LH pulse frequency before and after 7 d of oral estradiol and P. Main Outcome Measure: We measured the slope of the percentage reduction in LH pulse frequency as a function of d 7 P (slope). Results: Overall, Tanner 3-5 HA subjects were less sensitive to P-mediated slowing than Tanner 3-5 NC (slope, 4.7 ± 3.4 vs. 10.3 ± 7.7; P = 0.006). However, there was variability in the responses of HA subjects; 15 had P sensitivities within the range seen in NC, whereas nine were relatively P insensitive. The two groups had similar testosterone levels. Fasting insulin levels were higher in P-insensitive HA girls (39.6 ± 30.6 vs. 22.2 ± 13.9 μIU/ml; P = 0.02), and there was an inverse relationship between fasting insulin and P sensitivity in HA girls (P = 0.02). Tanner 1-2 NC had lower testosterone levels and were more P sensitive than Tanner 3-5 NC (slope, 19.3 ± 5.8; P = 0.04). Conclusions: Hyperandrogenism is variably associated with reduced GnRH pulse generator sensitivity to P-mediated slowing during adolescence. In addition to androgen levels, insulin resistance may modulate P sensitivity.